Processo de criação do espetáculo QUANTÉ: uma análise de vestígios - Ferreira, Thiago Xavier (2018)
This research aims to realize a reflexive analysis on the creation process of the play Quanté, created by Grupo Tripé from Uberlândia. This journey, therefore, wants to raise, identify and evaluate indications of a scenic intertextuality, a dialogue, between bordering languages, exploring the creative potential that each of these elements brought to the process and, consequently, to the work. In this way, we present some material and relevant data about the formation and acting dynamics of the group, as well as the description and analysis of constituent parameters of the work - which are: dramaturgy, the composition process and the process of structuring the scenes. We also present some thematic axes that were identified as basilar for the creation of the play Quanté, namely: body; space; game and collaborative process/collective creation. Finally, we organized a study with the reach and inferences that emerged from the research.